PENGOLAHAN SAMBAL IKAN TUNA SEBAGAI IMPLEMENTASI KULIAH KERJA NYATA DALAM PEMBERDAYAAN MASYARAKAT DESA PINOMONTIGA - Bakari, Yuliana; Nento, Wila Rumina; Wibowo, Larasati Sukmadewi; Samatowa, Lukman (Damhil: Jurnal Pengabdian kepada Masyarakat, 2023)
Thematic KKN in Pinomontiga village, Bone Bolango Regency, Bulawa District, is innovating to make tuna fish sauce products and providing education to the people of Pinomontiga village regarding the process of processing tuna fish sauce and how to market strategies for tuna fish sauce products.The activity of making tuna fish sauce products was carried out on Monday (28/8/2023), in the Pinomintiga Village Office Hall with the theme "Community Empowerment Through Post-Harvest Handling of Sea and Agricultural Products." This activity was attended by a number of Pinomontiga Village residents, Village Officials, and the Village Consultative Body (BPD).Keywords:Tuna Fish Sauce, Pinomontiga Village, Tuna Fish, Village Potential